2016
DOI: 10.1038/nature19352
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of kainate subtype glutamate receptor desensitization

Abstract: Glutamate receptors are ligand gated tetrameric ion channels that mediate synaptic transmission in the central nervous system. They are instrumental in vertebrate cognition and their dysfunction underlies diverse diseases1,2. In both the resting and desensitized states of AMPA and kainate subtype glutamate receptors the ion channels are closed while the ligand binding domain, which is physically coupled to the channel, adopts dramatically different conformations3–6. Without an atomic model for the desensitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
109
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 39 publications
17
109
0
Order By: Relevance
“…Given the apparent strengthening of desensitization in AMPARs carrying G725C and S729C substitutions (Armstrong et al, 2006; Plested and Mayer, 2009; Yelshanskaya et al, 2014) and weakening of desensitization by positive allosteric modulators and mutations at the D1-D1 interface (Gonzalez et al, 2010; Jin et al, 2005; Nayeem et al, 2009; Priel et al, 2006; Stern-Bach et al, 1998; Sun et al, 2002; Weston et al, 2006), such similarities supports the idea that the GluA2-2xGSG1L Quis structure represents a desensitized state. The latter conclusion is also consistent with transformation of the LBD layer assembly in GluA2-2xGSG1L ZK towards its more 4-fold symmetrical arrangement in GluA2-2xGSG1L Quis (Figure 6E–F,L), similar to the desensitized structure of GluK2 (Meyerson et al, 2016; Meyerson et al, 2014). …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Given the apparent strengthening of desensitization in AMPARs carrying G725C and S729C substitutions (Armstrong et al, 2006; Plested and Mayer, 2009; Yelshanskaya et al, 2014) and weakening of desensitization by positive allosteric modulators and mutations at the D1-D1 interface (Gonzalez et al, 2010; Jin et al, 2005; Nayeem et al, 2009; Priel et al, 2006; Stern-Bach et al, 1998; Sun et al, 2002; Weston et al, 2006), such similarities supports the idea that the GluA2-2xGSG1L Quis structure represents a desensitized state. The latter conclusion is also consistent with transformation of the LBD layer assembly in GluA2-2xGSG1L ZK towards its more 4-fold symmetrical arrangement in GluA2-2xGSG1L Quis (Figure 6E–F,L), similar to the desensitized structure of GluK2 (Meyerson et al, 2016; Meyerson et al, 2014). …”
Section: Resultssupporting
confidence: 83%
“…In contrast, the A/C LBDs in GluK2 bound to the full agonist (2S,4R)-4-methylglutamate are at similar positions as in the GluA2 NOW structure but the B/D LBDs rotate clockwise by 125° around their own axes (Figure 7C,F), presenting completely different surfaces at the intersubunit interfaces. As a result, helices E and G in the B/D LBDs, which do not contribute to intersubunit interfaces in the GluA2 structures, combine with helices E and G in subunits A and C of GluK2 to assemble a pseudo fourfold symmetric “desensitization ring” in the center of the LBD layer (Meyerson et al, 2016) (Figure 7F). Such a dramatic rearrangement of LBDs in GluK2 allows the M3 transmembrane segments in subunits B and D to adopt similar secondary structures as in subunits A and C (Figure 7I).…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine mutagenesis and electrophysiological studies carried out on the intact and ΔATD receptors, along with crystallographic studies on the isolated LBD ‘dimers’, suggested that rupture of the LBD dimer D1-D1 interface was sufficient to promote receptor desensitization (Armstrong et al, 2006). By contrast, cryo-EM studies of isolated AMPA receptors and the closely related kainate receptors suggest that there are, instead, large scale rearrangements of the LBD layer from 2-fold to ~4-fold symmetry (Meyerson et al, 2016; Meyerson et al, 2014). A low resolution x-ray study of an intact AMPA receptor, as well as cryo-EM studies, are also suggestive of large scale LBD rearrangements upon receptor desensitization (Dürr et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…In non-NMDARs, direct interactions between the ATD and LBD layers are minimal. Therefore, even if the ATDs undergo ligand-induced movements, there are few molecular routes for transduction of conformational changes and thus the ATDs of non-NMDARs do not markedly modulate ion channel gating (36, 4143, 52). By contrast, there are multiple distinct contacts between the ATD and LBD layers in NMDARs, and thus a number of mechanisms by which movements of the ATDs can be transduced to the LBD layer and, subsequently, to the TMD to modulate ion channel activity (38, 53, 54).…”
Section: Asymmetry Of Atd and Atd-lbd Interfacesmentioning
confidence: 99%